![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1/4 của 40m là:
40 : 1/4 = 160 ( m )
3/5 của 48 cm là:
48 : 3/5 = 80 ( cm )
10% của 4/5 kg là:
45 : 10 x 100= 450 ( kg )
1 và 2/13 = 15/13 ; 1 và 1/6 = 7/6
Vậy 15/13 của 7/6 m2 là:
7/6 : 15/13 = 91/90 ( m2)
Đ/s: ..........
~Hok tốt ~
![](https://rs.olm.vn/images/avt/0.png?1311)
a, Ta có : M= 1 - 2 + 3 -4 + 5-6 +... + 19 - 20
= ( 1-2 ) + ( 3 - 4 ) + ( 5-6 ) + ...+ ( 19 - 20 )
= ( -1 ) + ( -1 ) + ( -1 ) +...+ (-1 ) ( có 10 số ( - 1 )
= 10 . (-1 )
![](https://rs.olm.vn/images/avt/0.png?1311)
1.
a) \(\frac{13}{8}:\frac{13}{4}=\frac{1}{2}=0,5=50\%\)
b) \(12,5:2,5=5=500\%\)
~ Hok tốt ~
2.
\(\left(\frac{37}{9}+\frac{13}{4}\right).\frac{9}{4}+\frac{11}{4}\)
\(=\frac{265}{36}.\frac{9}{4}+\frac{11}{4}\)
\(=\frac{265}{16}+\frac{11}{4}\)
\(=\frac{309}{16}\)
\(1+\left(\frac{9}{10}-\frac{4}{5}\right):\frac{19}{6}\)
\(=1+\frac{1}{10}:\frac{19}{6}\)
\(=1+\frac{3}{95}\)
\(=\frac{98}{95}\)
\(\left(-7+\left|13\right|\right)-\left(13-\left|-7\right|-25\right)-\left(25+\left|-10\right|-9\right)\)
\(=\left(-7+13\right)-\left(13-7-25\right)-\left(25+10-9\right)\)
\(=-7+13-13+7+25-25-10+9\)
\(=\left(-7+7\right)+\left(13-13\right)+\left(25-25\right)-10+9\)
\(=0+0+0-10+9\)
\(=-10+9\)
\(=-1\)
~ Hok tốt ~
![](https://rs.olm.vn/images/avt/0.png?1311)
a; - \(\dfrac{10}{13}\) + \(\dfrac{5}{17}\) - \(\dfrac{3}{13}\) + \(\dfrac{12}{17}\) - \(\dfrac{11}{20}\)
= - (\(\dfrac{10}{13}\) + \(\dfrac{3}{13}\)) + (\(\dfrac{5}{17}\) + \(\dfrac{12}{17}\)) - \(\dfrac{11}{20}\)
= - 1 + 1 - \(\dfrac{11}{20}\)
= 0 - \(\dfrac{11}{20}\)
= - \(\dfrac{11}{20}\)
b; \(\dfrac{3}{4}\) + \(\dfrac{-5}{6}\) - \(\dfrac{11}{-12}\)
= \(\dfrac{9}{12}\) - \(\dfrac{10}{12}\) + \(\dfrac{11}{12}\)
= \(\dfrac{10}{12}\)
= \(\dfrac{5}{6}\)
c; [13.\(\dfrac{4}{9}\) + 2.\(\dfrac{1}{9}\)] - 3.\(\dfrac{4}{9}\)
= [\(\dfrac{52}{9}\) + \(\dfrac{2}{9}\)] - \(\dfrac{4}{3}\)
= \(\dfrac{54}{9}\) - \(\dfrac{4}{3}\)
= \(\dfrac{14}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
a)
\(A=\dfrac{-5}{6}\cdot\dfrac{3}{10}\\ =\dfrac{\left(-5\right)\cdot3}{6\cdot10}\\ =\dfrac{-1}{4}\)
b)
\(B=\dfrac{1}{3}-\dfrac{1}{4}+\dfrac{1}{12}\\ =\dfrac{4}{12}-\dfrac{3}{12}+\dfrac{1}{12}\\ =\dfrac{4-3+1}{12}\\ =\dfrac{1}{6}\)
Bài 2:
\(A=\left(\dfrac{-1}{5}\right)\cdot\dfrac{15}{4}+\left|\dfrac{4}{5}-\dfrac{14}{5}\right|:\dfrac{8}{3}\\ =\left(\dfrac{-1}{5}\right)\cdot\dfrac{15}{4}+\left|\dfrac{-10}{5}\right|\cdot\dfrac{3}{8}\\ =\left(\dfrac{-1}{5}\right)\cdot\dfrac{15}{4}+2\cdot\dfrac{3}{8}\\ =\dfrac{-3}{4}+\dfrac{3}{4}\\ =0\)
\(B=\left(\dfrac{-1}{2}\right)^2:1\dfrac{3}{8}+25\%\cdot\dfrac{3}{11}\\ =\left(\dfrac{-1}{2}\right)^2:\dfrac{11}{8}+\dfrac{3}{4}\cdot\dfrac{3}{11}\\ =\dfrac{1}{4}\cdot\dfrac{8}{11}+\dfrac{3}{4}\cdot\dfrac{3}{11}\\ =\dfrac{8}{44}+\dfrac{9}{44}\\ =\dfrac{17}{44}\)
\(C=\dfrac{-8}{5}+0,6+\left|\dfrac{-1}{2}\right|+\dfrac{1}{2}\\ =\dfrac{-8}{5}+\dfrac{3}{5}+\dfrac{1}{2}+\dfrac{1}{2}\\ =\left(\dfrac{-8}{5}+\dfrac{3}{8}\right)+\left(\dfrac{1}{2}+\dfrac{1}{2}\right)\\ =\left(-1\right)+1\\ =0\)
\(D=\dfrac{-5}{9}\cdot\dfrac{2}{13}+\dfrac{-5}{9}:\dfrac{13}{11}+1\dfrac{5}{9}\\ =\dfrac{-5}{9}\cdot\dfrac{2}{13}+\dfrac{-5}{9}\cdot\dfrac{11}{13}+\dfrac{14}{9}\\ =\dfrac{-5}{9}\cdot\left(\dfrac{2}{13}+\dfrac{11}{13}\right)+\dfrac{14}{9}\\ =\dfrac{-5}{9}\cdot1+\dfrac{14}{9}\\ =\dfrac{-5}{9}+\dfrac{14}{9}\\ =1\)